2010
DOI: 10.1371/journal.pntd.0000890
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices in Dengue Surveillance: A Report from the Asia-Pacific and Americas Dengue Prevention Boards

Abstract: BackgroundDengue fever is a virus infection that is spread by the Aedes aegypti mosquito and can cause severe disease especially in children. Dengue fever is a major problem in tropical and sub-tropical regions of the world.Methodology/Principal FindingsWe invited dengue experts from around the world to attend meetings to discuss dengue surveillance. We reviewed literature, heard detailed reports on surveillance programs, and shared expert opinions.ResultsPresentations by 22 countries were heard during the 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
184
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(188 citation statements)
references
References 17 publications
3
184
0
1
Order By: Relevance
“…In Mexico, serosurveys are not included in the dengue epidemiologic surveillance system. [10,11] According to the World Health Organization, active surveillance can provide an accurate and pertinent warning for Dengue epidemics that can improve the preventive strategies, but it is important to use it effectively for planning an effective response, while passive surveillance systems alone are ineffective for detecting an epidemic much before peak transmission. If we put the data we analyzed in the present study as an antecedent of what happened in the years following the last serosurvey, we can imply that if serosurveys were developed periodically, and if they included serotype specific immunity analyses (PRNT) along with vector surveillance, the Mexican epidemiologic bureau could have been able to predict early the outbreaks and it could have been able to plan specific strategies to reduce the burden of dengue in the region.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, serosurveys are not included in the dengue epidemiologic surveillance system. [10,11] According to the World Health Organization, active surveillance can provide an accurate and pertinent warning for Dengue epidemics that can improve the preventive strategies, but it is important to use it effectively for planning an effective response, while passive surveillance systems alone are ineffective for detecting an epidemic much before peak transmission. If we put the data we analyzed in the present study as an antecedent of what happened in the years following the last serosurvey, we can imply that if serosurveys were developed periodically, and if they included serotype specific immunity analyses (PRNT) along with vector surveillance, the Mexican epidemiologic bureau could have been able to predict early the outbreaks and it could have been able to plan specific strategies to reduce the burden of dengue in the region.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] Most estimates of dengue incidence in the region are based on hospital-based studies and nationally reported cases, which grossly underestimate the true burden of disease and infection. 31 We followed a cohort of 799 children in Colombo, Sri Lanka, and estimated the incidence of infection and disease to be 8.39 and 3.38 cases/100 children, respectively. The ratio of clinically inapparent to apparent infections was 1.48, which indicated that for every apparent infection there were approximately 1.5 inapparent infections in children.…”
Section: Discussionmentioning
confidence: 99%
“…Around 3.6 billion people are living under the risk of dengue infection [1] (http://www.who.int/denguecontrol/9789241504034/ en/). Average annual incidence of 20,474 dengue cases has reported in India during the tenure of 2006-2012 [18].…”
Section: Introductionmentioning
confidence: 99%